AJARAN PANCA SRADHA DALAM GEGURITAN BATUR TASKARA - I Putu Agus Aryatnaya Giri; Ni Luh Ardini; Ni Wayan Kertiani (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Geguritan Batur Taskara (hereinafter abbreviated as GBT) is one of the many literary works of geguritan in Bali, which is a Balinese cultural heritage, with the values of religious education, both moral values, philosophy / tattoos, and ritual values contained in in the literary work. The purpose of this research is to analyze the philosophical teachings / tattwa in Geguritan Batur Taskara using descriptive qualitative research methods. The conclusion of the research shows that the value of philosophy (tattwa) exists and is contained in the GBT with an outline of the five main points of belief in Hinduism called Panca Sradha. The five Sradha include; believe in the existence of Ida Sang Hyang Widhi Wasa (God Almighty), believe in the existence of atma (ancestral spiri